The Later Heidegger's Understanding and Critique of Metaphysics - Farr, David B.H. (My University, 1999)
This thesis investigates the later Heidegger's understanding and critique of metaphysics. Given the amount of work Heidegger published, it has been necessary to limit the focus of this thesis to two important texts. Each of these texts is examined twice: in PART I I garner Heidegger's understanding of metaphysics and in PART II I determine Heidegger' s critique of metaphysics. The first text considered here is the 1949 Einleitung, subtitled "Der Rtickgang in den Grund der Metaphysik", to the essay Was ist Metaphysik originally published in 1929. This essay has been translated by Walter Kaufmann as "The Way Back into the Ground of Metaphysics" in the monograph Existentialism from Dostoevsky to Sartre. The other text examined is Heidegger's Nietzsche. The first text was chosen for its succinct treatment of metaphysics and the second for its thoroughness.
It becomes clear throughout the thesis that Heidegger's understanding and critique of metaphysics can be summarized thus, "Metaphysics concerns itself only with beings (Seiende) as such". Although a traditional metaphysician may agree with this analysis, he or she may not understand why it is a critique. According to Heidegger it is a critique, because by focusing on beings (Seiende) metaphysis neglects or forgets Being (Sein). Once Heidegger's position and criticisms have been elucidated, some obstacles that arise for metaphysically based theology are briefly considered. The major obstacle is whether or not theology can talk about God in a non-objectifying manner. Can theology avoid making God one being among others in the same way that metaphysics reduces Being to one being among others? Heidegger urges Christian thinkers to heed the advice of their own scripture and not to seek knowledge of God through the wisdom of this world.
Keywords: Religious Studies; Religion; Religion